2014
DOI: 10.5897/ijbc2012.090
|View full text |Cite
|
Sign up to set email alerts
|

Gene duplication: A major force in evolution and bio-diversity

Abstract: Bridges reported one of the earliest observations of gene duplication from the doubling of a chromosomal band in a mutant of the fruit fly, Drosophila melanogaster, which exhibited extreme reduction in eye size. Based on whole-genome analysis of Arabidopsis thaliana, there is compelling evidence that angiosperms underwent two whole-genome duplication events early during their evolutionary history. Recent studies have shown that these events were crucial for the creation of many important developmental and regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The maintenance of gene copies of floral characters is usually justified as neofunctionalization (neoF) and subfunctionalization (subF) driven by positive selection3. Although balancing selection was suggested as one of the mechanisms for the maintenance of divergent (neoF) or complementary (subF) functions of functional gene copies45, several studies indicated that positive divergent selection and duplication events act as reciprocal evolutionary forces driving adaptive trait diversification67. Flagel and Wendel8 suggested that unequal crossing-over and/or gene conversion would homogenize duplicates, providing a means of amplifying adaptively important genes, with a tendency to accelerate the divergence of non-recombining clusters, and permitted gene family diversification and evolutionary plasticity cf.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance of gene copies of floral characters is usually justified as neofunctionalization (neoF) and subfunctionalization (subF) driven by positive selection3. Although balancing selection was suggested as one of the mechanisms for the maintenance of divergent (neoF) or complementary (subF) functions of functional gene copies45, several studies indicated that positive divergent selection and duplication events act as reciprocal evolutionary forces driving adaptive trait diversification67. Flagel and Wendel8 suggested that unequal crossing-over and/or gene conversion would homogenize duplicates, providing a means of amplifying adaptively important genes, with a tendency to accelerate the divergence of non-recombining clusters, and permitted gene family diversification and evolutionary plasticity cf.…”
mentioning
confidence: 99%
“…However, duplicated genes usually have only minor sequence variations that are sufficient to alter the substrate and product specificity but, thus, possess insufficient characteristics to predict their functional divergence1. On the other hand, both concerted evolution and purifying selection retained only small variations between paralogous genes for a long time, ensuring that the functional constraints of duplicated genes paralleled their expression in different tissues (i.e., subF)67.…”
mentioning
confidence: 99%